Angola : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2003)
Several years of high inflation rates have negatively affected economic conditions in Angola. Macroeconomic stabilization in Angola entails strict control over central bank credit to the government, an ending of the quasi-fiscal expenditures, and a reduction of the national bank of Angola's deficit. Reserve adequacy is an important factor for stable economic development and management. This note reviews some of the main challenges faced by Angola's policymakers in launching a credible subsidy reform, and also reviews the sources and uses of state oil revenue in Angola.